Electric and dielectric properties of a SiO2–Na2O–Nb2O5 glass subject to a controlled heat-treatment process - Graça, M.P.F.; Ferreira da Silva, M.G.; Sombra, A.S.B.; Valente, M.A. (Physica. B, Condensed matter, 2007)
Glass and glass ceramics with the molar composition 60SiO2-30Na2O-10Nb2O5 (mol%) were prepared by the melt-quenching method. Sodium niobate (NaNbO3) crystallites were precipitated on the surface of the glass through a controlled heat-treatment (HT) process. The NaNbO3 crystallites, detected by X-ray diffraction (XRD) in the 750 and 800 deg C HT sample, have scientific and technological interest due to their electrical and dielectrical properties and potential applications in microwave, pyroelectric and piezoelectric devices. Scanning electron microscopy (SEM), XRD, DC and AC conductivity and dielectric relaxation measurements were the techniques used to study these glass and glass ceramic materials. The dielectric properties of the glass ceramics have a strong dependence on the HT temperature. The number of particles, precipitated in the surface of the glass-ceramic samples, increases from the 650 to the 750 deg C samples and decreases in the 800 deg C sample. The size of the surface particles increases with the rise of the HT temperature. In the 750 and 800 deg C samples it was observed the presence of NaNbO3 particles. The DC (sigmaDC) and AC conductivity (sigmaAC) behaviour depends mainly of the number of network modifier ions in the glass matrix. The dielectric results are in agreement with the electric equivalent circuit formed by a three R/C (resistance in parallel with a capacitor element) serial model (two related with the sample surfaces and one with the bulk material). The dielectric relaxation data were fitted with a complex nonlinear least squares algorithm (CNLLS), which reveals that a resistor (R), in parallel with a constant phase element (CPE, ZCPE=1/[Q0(jw)n]), is a good equivalent circuit.